Genetic loci influencing C-reactive protein levels and coronary heart disease risk: results of genetic association and Mendelian randomisation study with meta-analysis in 80 614 people. (22nd September 2015) - Elliott, P; Chambers, JC; Zhang, W; Clarke, R; Peden, JF; Erdmann, J; Braund, P; Engert, J; Hopewell, J; Ashby, D; McCarthy, MI; Farrall, M; et al.
Abstract : Background: Plasma levels of C-reactive protein (CRP) are independently associated with the risk of coronary heart disease (CHD). Whether the relationship of CRP with CHD is causal, or whether CRP is simply an "innocent bystander" of the inflammatory disease process, is unknown. Methods: We first carried out a genome-wide association (n  =  17 967) and replication study (n  =  14 747) to identify genetic loci associated with plasma CRP concentrations. At each locus, we selected the most closely associated ("top-ranking") single nucleotide polymorphism (SNP) for testing against CHD. For the CRP locus, we then carried out a Mendelian randomisation experiment and meta-analysis with published studies, providing data for 21 876 cases and 58 738 controls. Results: Genetic variants in the CRP, LEPR, IL-6R, HNF1A and APOE-CI-CII loci were strongly associated with differences in CRP levels. Polymorphisms in LEPR (rs6700896), IL-6R (rs4537545) and APOE-CI-CII (rs4420638) were associated with the risk of CHD (p<0.002 and p<0.001). The associations between rs7553007 and other variants in the CRP locus with CHD risk were weak and non-significant. Interpretation: The weak association between variants in the CRP locus and CHD risk suggests that any causal association of CRP with atherosclerosis is likely to be small. We identify LEPR and IL-6R as putative new susceptibility loci for CHD.